Tracking the Acceleration Due to Gravity and Damping of a Pendulum: A Video Analysis - Pacala, Frank Angelo; Pili, Unofre (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
This study focused on using video analysis to track the acceleration due to gravity and damping of a pendulum. The video tracker analysis software was proven effective in collecting data from several physics experiments. This study offered new insights on using a tracker and combining it with MS Excel to generate a damping graph. A pendulum was set in motion and recorded with a high-speed camera from the iPhone 13. The footage was then analyzed using tracker video analysis, modeling software, and Microsoft Excel to determine the amplitude and frequency of the pendulum's motion. At the same time, the other variables were measured using traditional tools (e.g., the length of the yarn using a meter ruler). The measured values were then used to calculate the acceleration due to gravity and the damping constant of the system. The results showed that the acceleration due to gravity was consistent with the average accepted value, while the damping constant accurately represented what was seen from the generated graph. Overall, this study demonstrated the effectiveness of video analysis in tracking the behavior of physical systems and its potential applications in various fields.